Effectiveness of bait tubes for brown treesnake control on guam - Björn Lardner; Amy A. Yackel Adams; Julie A. Savidge; Gordon H. Rodda; Robert N. Reed; Craig S. Clark (Wildlife Society Bulletin)
ABSTRACT In 2008, we studied simulated toxicant efficacy to control invasive brown treesnakes (Boiga irregularis) using bait tubes (elongate bait stations that reduce non‐target bait take) in a 5‐ha enclosure in Guam (U.S. Territory) with a known population of snakes. Instead of toxicants, we implanted radiotransmitters in small (6.6 ± 1.4 g) and large (21.8 ± 2.9 g) bait‐mouse carcasses, offered from 2 types of bait tubes over a 3‐month period. The known snake population allowed us to characterize not only the snakes taking bait, but also those evading our mock control effort. Tube design had no effect on take rate, but snout–vent length was a strong predictor of bait take: none of the 30 snakes <843 mm in length took any bait, whereas 77 of the 126 snakes ≥843 mm in length took 164 baits. While medium‐sized snakes preferentially ingested small bait (and the largest snakes tended to take large mice more frequently), some of the smallest snakes that took bait ingested large mice. Snake body condition was positively correlated to take rate, but snake sex had no discernible effect. Our data show that there is a relatively narrow size (and, thus, time) gap between the size at which the snakes become susceptible to bait‐mouse take and the size at which they become sexually mature. This has implications for the timing of repeated baiting efforts, if the goal is eradication rather than suppression. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.